Front Cover Advanced Engineering Materials 5/2013. Issue 5 (2nd May 2013) - Chen, Biao; Shi, Tielin; Li, Mo; Zhang, Zhaobo; Zhu, Zhijing; Liao, Guanglan
<x xml:space="preserve">Abstract</x> The cover shows Laser welding of Zr41Ti14Cu12Ni10Be23 bulk metallic glass and temperature field simulation. For further details see the article by Guanglan Liao et al. on page 407. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>